Rehabilitation of partially-failed reinforced concrete beam by using aluminium coil - Ho, Wai Kei (2016)
Strengthening of existing reinforced concrete beams is one of the best solutions applied globally in construction field to partially-failed building elements. This paper presents an experimental study aims to investigate the flexural behavior of reinforced concrete beams strengthened by bolting layers of aluminium coil to the beams’ soffit. Beam samples were loaded until they have reached partially-failed condition and strengthened by bolting different thickness of 0.6 mm, 1.2 mm and 1.8 mm aluminium laminates. Then each was tested to failure in four point bending over a clear span length of 1500 mm and one sample was not strengthened with any aluminium laminates and served as a control beam. Test results clearly illustrated the application of aluminium laminates to the tension surface of the reinforced concrete beam has enhanced its ultimate load capacity. It was observed that as the number of layers of aluminium laminates increases, the ultimate load capacity of beams increases accordingly. Therefore, this retrofitting method of construction could be utilized as one of the ways in strengthening partially-failed reinforced concrete beams.